Ancestors, inter-generational transmission of attitudes, and corporate performance: Evidence from the Italian Mass Migration - Erminia Florio; Stefano Manfredonia (Global Labor Organization (GLO), 2021)
We study the effect of the attitudes of a CEO's ancestors on firm performance. To do so, we collect detailed information on emigrants from Italian municipalities during the Age of Mass Migration (1892-1924) from Ellis Island ships lists and use emigration experience as a proxy for ancestors' risk propensity. We adopt an epidemiological approach complemented with an instrumental variables strategy and find that Italian firms managed by a CEO that belongs to a family with past emigration experience tend to perform better and to be more productive. In line with an inter-generational transmission of attitudes hypothesis, we show a positive relationship between the emigration experience of a CEO's ancestors and alternative measures of corporate risk-taking. The attitudes of a CEO's ancestors have as well consequences on firm solvency and on the cost of capital.
Keywords: G30; M14; Z1; 330; Emigration; Attitudes; Corporate Performance; Mass Migration